SELF-AWARENESS MOVEMENT: DERADICALIZATION OF STUDENTS' RELIGION UNDERSTANDING IN LAMPUNG PROVINCE - Murdiana, Elfa; Sudiono, Titut (AKADEMIKA: Jurnal Pemikiran Islam, 2019)
Abstract This research analyses the concept of leadership within transnational Islam tradition in Indonesia and their response towards democracy, particularly within three largest transnational organizations of Jama’ah Tabligh, Jama’ah Tarbiyah, and Hizbut Tahrir Indonesia (HTI). Based on an extensive literature study and in depth interviews, this research found that: first, leadership concept in the tradition of (1) Jamaah Tabligh is called “Amir” which is appointed through a dialogue (musyawarah). The Amir is responsible to preach ‘the da’wah ‘ala> Minhaj an-Nubuwwah (proselytizing Islam using Prophetic methods) through ‘khuru>j fi> sabi>lilla>h; (2) Jama’ah Tarbiyah is called “Majlis Syuro” as the highest body of the Islamic party which functions as “ahlul halli wal ‘aqdi” (the consultative assembly) in its political movement represented by Partai Keadilan Sejahtera (Prosperous Justice Party/ PKS); and (3) HTI is called “Khalifah” that calls for the system of ‘Khila>fah ‘ala> Minha>ji an-Nubuwwah’. Second, those three organizations have divergent responses regarding the practice of democracy in Indonesia. The responses are (1) Jamaah Tabligh chooses to be apolitical and let its followers whether to participate in the democracy or not; (2) Jamaah Tarbiyah supports the democracy system by establishing Prosperous Justice Party (PKS), and (3) HTI opposes democracy because the concept is born from the capitalist ideology, a kufr system as it created by human and is not taken from Shari’ah concept.. Keywords: Leadership. Transnasional, and Democracy